Comparison of PCR-based profiling techniques for the identification of tetraploid potato (Solanum tuberosum L.) cultivars - Lambert, Carol-Ann (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1998.